Improving Quality of Care for Hospitalized Smokers with HIV: Tobacco Dependence Treatment Referral and Utilization - Fitzgerald, Sharon A. (Jt Comm J Qual Patient Saf, 2016)
BACKGROUND: Most persons living with HIV smoke cigarettes and tend to be highly dependent, heavy smokers. Few such persons receive tobacco treatment, and many die from tobacco-related illness. Although advancements in antiretroviral therapy (ART) have increased the quality and quantity of life, the health harms from tobacco use diminish these gains. Without cessation assistance, thousands will benefit from costly ART, only to suffer the consequences of tobacco-related disease and death. A study was conducted to examine in detail inpatient tobacco treatment for smokers with HIV. METHODS: Data collected at hospital admission and data collected by tobacco treatment specialists were examined retrospectively for all inpatients with HIV who were admitted to an academic medical center for a five-year period. Specifically, the prevalence of cigarette smoking, factors predictive of referral to tobacco treatment, referral for tobacco treatment, treatment participation, and abstinence at six months post-treatment were measured. Differences in referral and treatment participation between all smokers and smokers with HIV were also assessed. RESULTS: Among the 422 admitted persons with HIV, 54.5% smoked and 21.7% were referred to inpatient tobacco treatment services. Substance abuse and tobacco-related diagnoses were predictive of referral to inpatient tobacco treatment specialists. Among the 14 treatment participants reached for follow-up, 11 (78.6%) made quit attempts and 3 (21.4%) reported abstinence. Smokers with HIV were less likely to be referred to and treated by tobacco treatment services than all smokers admitted during the same time frame. CONCLUSIONS: Although tobacco is a major cause of mortality, few smokers with HIV are offered treatment during hospitalization. Those who are treated attempt to quit. Hospitalization offers a prime opportunity for initiating smoking cessation among those with HIV.